A theoretical investigation on End-of-Life (EOL) product collection methods in a closed-loop logistics network - Lamsali, Hendrik; Ariffin, Ahmad Shabudin (Scientific & Academic Publishing, 2013)
The importance of reverse logistics is evident in various industries.The benefits of reverse logistics and product recovery have also been highlighted in previous theoretical investigations.The motivations of its implementation are generally divided into legal, economic and socio-environmental factors. One of the crucial components of a reverse logistics system is product return channels. The success of other components especially the recovery operations depends on the performance of the return channels. Although numerous investigations on product return channels have been carried out, research on some critical aspects remains wanting. This study presents a review that highlights this deficiency; depicts latest research development on product return channels, relevant decisions making issues and direction for future research. The review emphasizes on the collection methods of drop-off, pick-up and mail return as the main return avenues that have largely been neglected in the previous research. At the end of the study, we propose a new closed-loop logistics network and future research propositions.